Mineralization of the sulfonated azo dye Mordant Yellow 3 by a 6-aminonaphthalene-2-sulfonate-degrading bacterial consortium. - Haug, W (1991)
Under anaerobic conditions the sulfonated azo dye Mordant Yellow 3 was reduced by the biomass of a bacterial consortium grown aerobically with 6-aminonaphthalene-2-sulfonic acid. Stoichiometric amounts of the aromatic amines 6-aminonaphthalene-2-sulfonate and 5-aminosalicylate were generated and excreted into the medium. After re-aeration of the culture, these amines were mineralized by different members of the bacterial culture. Thus, total degradation of a sulfonated azo dye was achieved by using an alternating anaerobic-aerobic treatment. The ability of the mixed bacterial culture to reduce the azo dye was correlated with the presence of strain BN6, which possessed the ability to oxidize various naphthalenesulfonic acids. It is suggested that strain BN6 has a transport system for naphthalenesulfonic acids which also catalyzes uptake of sulfonated azo dyes. These dyes are then gratuitously reduced in the cytoplasm by unspecific reductases.